Influence of Compression Thresholds and Maximum Power Output on Speech Understanding with Bone-Anchored Hearing Systems. (22nd October 2021) - Gawliczek, Tom; Wimmer, Wilhelm; Caversaccio, Marco; Kompis, Martin
Abstract : Bone-anchored hearing systems (BAHS) transmit sound via osseointegrated implants behind the ear. They are used to treat patients with conductive or mixed hearing loss, but speech understanding may be limited especially in users with substantial additional cochlear hearing losses. In recent years, BAHS with higher maximum power output (MPO) and more advanced digital processing including loudness compression have become available. These features may be useful to increase speech understanding in users with mixed hearing loss. We have tested the effect of 4 combinations of two different MPO levels (highest level available and level reduced by 12 dB) and two different compression thresholds (CT) levels (50 dB and 65 dB sound pressure level) in 12 adult BAHS users on speech understanding in quiet and in noise. We have found that speech understanding in quiet was not influenced significantly by any of the changes in these two fitting parameters. In contrast, in users with average bone-conduction (BC) threshold of 25 dB or more, speech understanding in noise was improved by +0.8 dB to +1.1 dB (p < 0.03 ) when using the higher MPO level. In this user group, there may be an additional, but very small benefit of +0.1 dB to +0.4 dB when using the lower rather than the higher CT value, but the difference was not statistically significant (p > 0.27 ). In users with better average BC thresholds than 25 dB, none of the improvement was statistically significant. Higher MPOs and possibly, to a lesser degree, lower CTs seem to be able to improve speech understanding in noise in users with higher BC thresholds, but even their combined effect seems to be limited.